LEGAL ANALYSIS OF DRUG ABUSE LAW TREATMENT THROUGH A RESTORATIVE JUSTICE APPROACH TO THE COUNTRY'S ECONOMY - Ariel Hermanus Gumalang; Lesza Lombok; Feibe Engeline Pijoh (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2025)
Law evolves continually from the past to the present, aiming to improve various aspects, particularly the implementation of justice. One significant development is Restorative Justice, which shifts the focus in the criminal justice system towards justice for both victims and perpetrators, including alternative punishments like social work. The term